Control of lipopolysaccharide-high-density lipoprotein interactions by an acute-phase reactant in human serum. - Tobias, P S (1985)
We have recently described several phenomena involving the interactions of lipopolysaccharides (LPS) from Salmonella minnesota Re595 (Re595-LPS) with rabbit serum, which are different in and unique to acute-phase serum as compared with normal serum (P.S. Tobias and R.J. Ulevitch, J. Immunol. 131:1913-1916, 1983). To determine whether these phenomena could also be observed in acute-phase human serum (APHS), we used APHS obtained from volunteers injected with etiocholanolone. As observed in acute-phase rabbit serum, we found that (i) in APHS, Re595-LPS forms a protein complex with a density of 1.3 g/cm3 which does not form in normal human serum (NHS), (ii) in APHS, the t1/2 for LPS-high-density lipoprotein (HDL) complexation is at least a factor of 10 slower than the t1/2 for LPS-HDL complexation in NHS, (iii) when Re595-LPS serum mixtures are dialyzed against a low salt buffer, Re595-LPS precipitates in less soluble form from APHS than from NHS, and (iv) the precipitate from Re595-LPS-APHS mixtures includes a protein with a molecular weight of approximately 60,000 which does not precipitate from Re595-LPS-NHS mixtures or from NHS or APHS alone. These indications of an altered status of LPS in NHS and APHS suggest that one or more acute-phase reactants interact with Re595-LPS to modify its rate of binding to HDL.